Effect of Heavy Metals on the Andrographolide Content, Phytochemicals and Antioxidant Activity of Andrographis paniculata - Antony, Anna; Nagella, Praveen (Asian Journal of Chemistry, 2020)
Andrographis paniculata is a medicinal plant that has several medicinal properties and has been traditionally used in different medicinal preparations. The present study deals with the influence of heavy metals (lead, mercury and silver) on andrographolide, phytochemicals and antioxidant activity in Andrographis paniculata. Two months old saplings were subjected to heavy metal stress of two different concentrations (0.2 mM and 0.4 mM) for three different times at 3 day time interval. The results showed that the saplings treated with heavy metals showed increased concentration of andrographolide content. The saplings treated with 0.4 mM silver showed the highest increase in the andrographolide content (24.58 ± 2.85 mg/g of DW) compared with control (9.41 ± 1.26 mg/g of DW) and other treatments. Variations in the biochemical parameters like total phenolic content, total flavonoid content, etc. were also prominent with all the treated samples when compared to that of control.